2019
DOI: 10.1007/978-3-030-00817-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Ion Dynamics: Implications for Potassium Buffering and Liquid Flow

Abstract: We review modeling of astrocyte ion dynamics with a specific focus on the implications of socalled spatial potassium buffering where excess potassium in the extracellular space (ECS) is transported away to prevent pathological neural spiking. The recently introduced Kirchoff-Nernst-Planck (KNP) scheme for modeling ion dynamics in astrocytes (and brain tissue in general) is outlined and used to study such spatial buffering. We next describe how the ion dynamics of astrocytes may regulate microscopic liquid flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…To calculate the osmotically induced volume changes dV/dt, we used the formalism outlined in [51]. The water flow Q across the membrane is given by…”
Section: Volume Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the osmotically induced volume changes dV/dt, we used the formalism outlined in [51]. The water flow Q across the membrane is given by…”
Section: Volume Dynamicsmentioning
confidence: 99%
“…Furthermore, when ion concentrations change in neurons, astrocytes, and the ECS, it will cause osmotic pressure gradients over the cellular membrane. This can lead to cellular swelling or shrinkage [48][49][50][51], which in turn will alter the ionic concentrations in the swollen or shrunken volumes. Cellular swelling and a corresponding shrinkage of the ECS is, for example, an important trademark of pathological conditions such as seizures and spreading depression [52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when ion concentrations change in neurons, astrocytes, and the ECS, it will cause osmotic pressure gradients over the cellular membrane. This can lead to cellular swelling or shrinkage [39][40][41][42], which in turn will alter the ionic concentrations in the swollen or shrunken volumes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ionic diffusion between astrocytes is mediated by gap junction channels, which create narrow passages, leading to a Poissonian law for the exchange rate (Holcman and Schuss, 2013). Such local description emphasizes the global electrodiffusion here simulated during either dynamical changes induced by neuronal activity or during subsequent steady states (Ostby et al, 2009;Oyehaug et al, 2012;Halnes et al, 2013;Halnes et al, 2016). Osmotic pressures and aquaporin4 (AQ4) water based fluxes are also simulated and are proposed to account for changes in both astrocytic swelling and ECS volume.…”
Section: Computational Modeling Of Astroglial Regulation Of Extracellmentioning
confidence: 97%
“…Such approach showed that astrocytes can control extracellular levels of K + and glutamate solely during mild ischemia. Interestingly, more recent modeling studies on astrocyte ion dynamics and implications of spatial K + buffering put forward a multiscale theory that includes not only local ionic exchanges and diffusive processes, but also osmotic changes and volume regulations (Ostby et al, 2009;Oyehaug et al, 2012;Halnes et al, 2013;Halnes et al, 2016). This model indeed proposes that astroglial ion dynamics might modulate microscopic liquid flow via osmotic effects resulting in whole-brain macroscopic flow.…”
Section: Computational Modeling Of Astroglial Regulation Of Extracellmentioning
confidence: 99%